Сучасні технологічні побудови для виробництва прокату з міді та її сплавів на базі концепції мікро-металургійних заводів - Смірнов, О.М.; Нарівський, А.В.; Верзілов, О.П.; Смірнов, Ю.О.; Семенко, А.Ю. (Physico-technological Institute of Metals and Alloys, 2023)
The reasons of low efficiency of metallurgical plants on processing of non-ferrous metals, weaknesses of technological constructions on the basis of the concept of metallurgical mini-plants and competitive advantages of productions on the basis of the concept of micro-plants are shown. The processes of reducing production capacity in new non-ferrous metallurgy plants are considered. “Conform” and “UPCAST” processes are considered in detail from the point of view of their technological construction, advantages and possibilities of use of these processes in the conditions of domestic production of copper. The article notes that the sharp decline in domestic consumption of copper and its alloys due to the crisis of the last century provoked a reduction in scrap collection and, consequently, a reduction in scrap spreads, raised domestic prices in scrap metal in Ukraine and Russia almost worldwide. This, in turn, led to a tendency to significantly reduce the profitability of minifactories. Dynamically developing industries are constantly increasing the requirements for the quality of rolled copper and its alloys. This trend forces manufacturers to prefer copper electrolytic refining as a raw material. Current trends in copper scrap prices, growing demands for product quality from consumers, the availability of equipment from Chinese manufacturers for new technological constructions and reduced consumption create the preconditions for the construction of efficient micro-metallurgical plants with production of 3–5 thousand tons per year, targeted at the regional consumer and used as raw material or publicly available cathode copper, or cast billet produced in “UPCAST” installations. Such constructions have an order of magnitude lower overhead costs, a shorter technological chain, which determines the short production time and higher quality indicators of the products in comparison with non-ferrous metal processing plants.